PERSEKUTUAN SEMPURNA ALLAH TRITUNGGAL SEBAGAI BASIS PEMBEBASAN MASYARAKAT DALAM RADIKALISME AGAMA - Tomy Taroreh (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2022)
Differences can create problems in diversity. Anti-union and hatred of incompatible thoughts can result in coercion and violence. Religious radicalism in the state is able to break up unity and injustice in people's lives. Based on a critical and analytical literature study, a model of life for diverse societies was found based on the concept of perikhoresis in the perfect communion of the Triune God. Communio, a community in which individuals form communion with one another. A form of relevant partnership model in Indonesian society with the aim of creating a form of general welfare in the midst of diversity.